Economic Aspects of Cash Access Problems - Arkadiusz Manikowski (European Management Studies)
Purpose: The aim of the article is to examine if difficulty of access to cash may influence the financial exclusion in Poland. Design/methodology/approach: The analysis was performed using microdata collected in the survey on payment habits of Polish consumers and spatial data on ATMs locations. Estimated distance to points where cash can be withdrawn together with feature of respondents of the state of possession of a payment account helps to identify relationships between access to cash and financial exclusion. To prove significance of the relationship, a statistical test is used. Findings: The Covid-19 pandemic has highlighted the existence of a real risk associated with the problem of the physical availability of cash. which is caused by the systematic reduction of the network of ATMs and commercial bank branches handling cash, which are the main points where consumers can withdraw it. This may consequently lead to financial and social exclusion of certain groups of consumers for whom cash is the main, or even the only, means of making payments. Results support the thesis that payment account without (real) option of easy access to cash may discourage consumers from opening the account and contribute to increased financial exclusion. It is especially visible in rural regions and small towns where we observe high level of exclusion (lack of payment accounts) and longer distance to the nearest ATM. Research limitations/implications: The presented results were based on simple statistical analyses. Further research should include econometric modeling using logit/probit models. Originality/value: The obtained results are the first on the impact of access to cash on financial exclusion in Poland and consistent with the situation in other European countries. The results allow to show the importance of access to physical money in a broader context than just having means of payment to pay for purchases.